RESEARCH FOR DISTRIBUTION OF DATA FROM RISK TECHNICAL SYSTEMS - Petrov, Nikolay; Panayotova, Galina (International Journal of Computing, 2014)
In control measurements as a result of the inevitable process of aging where the average value of the measured parameters of the risk technical systems are changing uninterrupted. That is defined by the technical impossibility for their complete recovery. As a result the measured parameters are functions of the period of technical exploitation. Because of an analogue processes in the periodical series of control measuring and its root-mean square diversion are also functions of the period of technical exploitation.